Pengembangan Masyarakat Islam dalam Sistem Dakwah Islamiyah - Aliyudin, Mukhlis (Jurnal Ilmu Dakwah, 2009)
For moslem community, daâwah hold essential role with the importance for with development, and even that daâwah the reality is development. Amends and dont it a community (ummat) really hinges on intensity and daâwah quality that did by moslems. With daâwah moslems can get role in engineers the moslem community social living well in social, economy, culture, politics, even itâs no impossible will make them as â trend setted â and main factor and actor in changed social development. Daâwah constitutes aware job in order to uphold justice, increasing welfare, enriching equation, and reaches happiness.